Does it matter how you play? The effects of collaboration and competition among players of human computation games - Pe‐Than, Ei Pa Pa; Goh, Dion Hoe‐Lian; Lee, Chei Sian (Journal of the American Society for Information Science and Technology, 2017)
Human computation games (HCGs) harness human intelligence through enjoyable gameplay to address computational problems that are beyond the power of computer programs but trivial for humans. With the popularity of crowdsourcing, different types of HCGs have been developed using various gameplay mechanics to attract online users to contribute outputs. Two commonly used mechanics are collaboration and competition. Yet there is little research examining whether HCGs perform better than nongame applications in terms of motivations and perceptions. Thus, this study investigates the effects of collaborative and competitive mechanics on intrinsic motivation and perceived output quality in mobile content sharing HCGs. Using a within‐subjects experiment, 160 participants were recruited from 2 local universities. The findings suggest that the nongame application was perceived to yield better quality output than both HCGs, but the latter offered a greater satisfaction of motivational needs, which may motivate individuals to continue playing them. Taken together, the present findings inform researchers and designers of HCGs that games could serve as a motivator to encourage participation. However, the usefulness of HCGs may be dependent on how one can effectively manage the entertainment–output generation duality of such games. This article concludes by presenting implications, limitations, and future research directions.